Durability and FTIR Characteristics of Sustainable Bacterial Concrete with Mineral Admixtures - R. Porselvan; T. S. Lakshmi; Muniyandi Tholkapiyan (Журнал інженерних наук)
The objective of this study is to optimize the concentrations of bacillus megaterium (BM), alccofine (AF), and silica fume (SF) in self-healing concrete while controlling the content of manufactured sand (M-sand). This research addresses the pressing need for sustainable alternatives to traditional cement as excessive energy consumption and environmental impacts continue challenging the construction industry. A novel “binary and ternary blended cementitious system” was developed, featuring twelve distinct mix proportions. M-sand was fully utilized as an acceptable aggregate substitute, with bacterial concentrations of (10–50)·105 cells/ml incorporated to mitigate crack formation. Cement was partially replaced with AF, and the M-sand content was adjusted from 0 to 20 % in 5 % increments. This study also uniquely evaluates the durability properties of the various cementitious systems, including water absorption, concrete density, porosity, long-term strength retention, and rapid chloride permeability – at intervals of 7, 14, and 28 days post-curing. Fourier transform-infrared spectroscopy (FTIR) was employed to analyze calcite precipitation, providing insights into the biochemical mechanisms. The results indicate that while SF demonstrates superior effectiveness compared to AF, combining both enhances durability compared to alternative mixes. The findings reveal that bacterial concrete incorporating zeolites can significantly improve structural strength and be a sustainable building material. Notably, incorporating additional cementitious materials with mineral admixtures increased strength by up to 10 % through optimized bacterial concentrations. The successful precipitation of calcium carbonate confirmed the beneficial properties of the bacterial agents, which are safe and non-toxic to the environment. Overall, this study contributes valuable knowledge on reducing cement usage and carbon dioxide emissions, positioning BM, alongside AF and SF, as a promising approach for environmentally friendly concrete solutions.